2021
DOI: 10.1186/s12913-021-06201-0
|View full text |Cite
|
Sign up to set email alerts
|

Brexit and European doctors’ decisions to leave the United Kingdom: a qualitative analysis of free-text questionnaire comments

Abstract: Background Quantitative evidence suggests that Brexit has had a severe and negative impact on European doctors, with many medical staff leaving the UK. This study provides a detailed examination of European doctors’ feelings towards Brexit, their intentions to leave the UK, and factors that may contribute to their potential decisions to migrate. Methods An online questionnaire which included three optional free-text questions explored self-identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These barriers are particularly relevant for EU doctors in the BREXIT era. The fact that EU doctors qualifications are now not automatically recognised in the UK means the number of doctors migrating to the UK from the EU could decrease [ 70 , 71 ]. Recent projections are that Brexit has resulted in 4,285 fewer European doctors coming to the UK [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These barriers are particularly relevant for EU doctors in the BREXIT era. The fact that EU doctors qualifications are now not automatically recognised in the UK means the number of doctors migrating to the UK from the EU could decrease [ 70 , 71 ]. Recent projections are that Brexit has resulted in 4,285 fewer European doctors coming to the UK [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data are presented on IMG migration in the Netherlands. These migration flows show that migration patterns differ strongly within these two EU-countries Quantitative UK 1.18, 1.5, 1.40, 2.1, 2.4, 3.17, 3.24 25 Hosni [ 50 ] 2017 To find out if doctors leaving the UK at the end of the 2 year "International Doctors Training Programme of Obstetrics and Gynaecology" feel that they achieved what they expected to achieve, what went well and what did not go well Quantitative UK 2.19, 2.10, 2.1, 3.2 26 Iacobucci [ 14 ] 2017 To explore if EU doctors are considering leaving UK Quantitative UK 1.30, 1.35, 1.42, 27 Lambert [ 34 ] 2017 To report the changes to UK medicine which doctors who have emigrated tell us would increase their likelihood of returning to a career in UK medicine Quantitative UK 1.14, 1.15, 1.16, 1.18, 2.20, 2.25, 2.17, 3.17, 3.1, 3.15, 3.4, 3.6 4.21, 5.14 28 Legido-Quigley [ 27 ] 2015 To describe the experiences of doctors who decide to move to the UK from other EU member states, exploring their motivations for moving and their experiences of registering and working in the UK Qualitative UK 1.13, 1.5, 2.1, 2.4, 3.17, 3.24, 3.12, 3.9 4.1, 4.12, 4.26, 6.22, 5.16 29 Milner [ 71 ] 2021 To assess how Brexit relates to doctors’ migration intentions in relation to their feelings that Brexit has impacted their professional life, national identity, and demographic factors Quantitative UK 1.35 …”
Section: Appendix Cmentioning
confidence: 99%
“…EEA academics may be particularly attracted to apply for these posts, as there may not be similar academic training pathways in Europe. However now the Brexit transition period has ended, the automatic recognition of EEA professional qualifications in the UK no longer exists17 which may have a significant impact on the demographics of UK IAT workforce going forwards. There is growing evidence that diversity among academic teams results in improved performance, creativity and impactful research,10 18 19 and it is extremely important that the academic training pathways encourage a diverse pool of applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Indicatively, a survey-based, cross-sectional study of 1,172 doctors found that 79.4% of respondents voted to remain in the EU in the 2016 referendum compared with 48.1% of voters as a whole (P<0.001), while the median score for the impact of Brexit on the NHS on a scale of 0 (worst) to 10 (best) was 2 (interquartile range, 1-4) (10). There is already some evidence suggesting that European doctors are leaving the UK because of Brexit and its consequences, including work pressure and understaffing (4). In a survey conducted in 2019, 63% of higher specialist doctors and 40% of consultants reported daily or weekly gaps in hospital medical cover (11).…”
Section: Challenges Of Brexitmentioning
confidence: 98%